Perancangan Komputerisasi Analisis Kuantitatif Pendokumentasian Rekam Medis di UPTD Puskesmas Dompu Kota - Martinus Siswahyudhi Wiratomo; Trismianto Asmo Sutrisno; Astri Sri Wariyanti (Institut Informatika dan Bisnis Darmajaya, 2023)
Medical records can be used for various purposes with the condition that they must be of good quality. To maintain the quality of medical records, medical record analysis must be carried out periodically. To support medical record analysis activities, it is necessary to use technology and information. The purpose of this study was to design a computerized quantitative analysis of medical record documentation at the UPTD Puskesmas Dompu Kota.This type of research is research and development, the development method uses the waterfall method. Medical record analysis used quantitative analysis of medical records. How to collect data by observation and unstructured interviews. The programming language used is PHP while the database uses MySQL. Functional testing yields a value of 1 and efficiency testing using the GTmetrix tool with an Overal score of A, i.e. the higher the grade the better the performance, Performance 98% The higher the percentage the faster, Structure 95% The higher the percentage the better the design, lCP 0.81 seconds Maximum limit 1.2 seconds, TBT 0 seconds Maximum limit 0.15, CLS 0 seconds Maximum limit 0.1 seconds.Based on the functionality testing and GTmetrix testing, it can be concluded that the design of computerized analysis of medical record documentation at the UPTD Puskesmas Dompu Kota can be used to support medical record analysis activities